Ultrafast nonlinear spectroscopy of individual quantum dots: imaging and coherent coupling - Kasprzak, J; Patton, B; Langbein, W (2008)
We review our recent advances in four-wave mixing spectroscopy of individual semiconductor quantum dots using heterodyne spectral interferometry, a novel implementation of transient nonlinear spectroscopy allowing the study of the transient nonlinear polarization emitted from individual electronic transitions in both amplitude and phase. We present experiments on individual excitonic transitions localized in monolayer islands of a GaAs/AlAs quantum well. The detection of amplitude and phase allows the implementation of a twodimensional femtosecond spectroscopy, in which mutual coherent coupling of single quantum dot states can be observed and quantified. By combining two-dimensional femtosecond spectroscopy with four-wave mixing mapping in the real space we found coherent coupling between spatially separated excitons by up to ~ 0.8 μm..